Ciało jako miejsce rozwoju - Cristina Sa Carvalho (Jesuit University Ignatianum in Krakow, 2017)
For children and adolescents, life is continuous growth and change. Genetic inheritance interacts with individual experiences and learning opportunities. Some scholars focused their attention in the body and mind relation and try to understand the development as an interaction between genetics and environmental factors, because human mind is not separated from the body experience and the body structures. William James advocated that our emotions are tied in with our bodily experiences; even so the physiological processes are modeled by the social and psychological phenomena. Without our bodies, there can be no consciousness, which is at heart a mechanism for survival that engages the body, emotion and mind in the spiral of human life.